EFL Students' Perception of Google Translate as a Translation Tool - Fatkhurozi, Anang; Hidayat, Rohmat (Journal of Linguistics and Social Studies, 2024)
This study aims to explore students' perceptions of the use of Google Translate in learning English as a foreign language (EFL). In the context of globalization and digitalization, digital translation tools such as Google Translate have become an important component in the language learning process. Qualitative research methods are used to obtain an in-depth understanding of how students at STAI Nurul Islam Mojokerto, English Language Education Study Program view the effectiveness and usefulness of Google Translate. Data were collected through questionnaires and interviews with 50 students from semesters V and VII. The results showed that students often used Google Translate to facilitate text comprehension and complete assignments, but also had concerns about accuracy and reliance on the tool. These findings indicate that while Google Translate offers convenience and efficiency, its use needs to be balanced with authentic language practice to avoid a negative impact on the development of deep language skills. This research provides important insights into how digital translation technology affects the language learning experience and suggests the need for adjustments in teaching methods to optimize the use of translation tools in English learning.